Benefits and Challenges to “Period Policies” – Menstruating Individuals Are Empowered Through Inclusive Dialogue and Advocacy - Leahy, Stevie (Columbia Journal of Gender and Law, 2021)
The governing laws within the United States center the experience of white, cis- gender, able-bodied males and largely ignore the existence and experience of menstruating individuals within the workplace. Despite the progress made since Judy Blume’s watershed novel, Are You There, God? It’s Me, Margaret, the topic of menstruation is still avoided, shamed, stigmatized, and misunderstood. One possibility to advance the rights of menstruating individuals and recognize these cyclical realities is menstrual leave, or “period policies.” The goal of this type of legislation is to address the intersectional indignities of menstrual injustice and normalize periods through more accommodating employment regulations. However, the dialogue surrounding these policies has been limited and risks leaving behind individuals who are already excluded from many workplace protections, compounding the discrimination and disparate treatment experienced.